Epidemiology of Marfan syndrome: a retrospective cohort study based on the Korean population - Shin Yi Jang; June Huh; Duk-Kyung Kim; Taek Kyu Park (Precision and Future Medicine, 2024)
Purpose This study aimed to determine the risk of incidence, prevalence, survival, and death risk for Marfan syndrome (MFS) in Korea. Methods MFS (10th revision of the International Statistical Classification of Diseases [ICD-10] code: Q87.4) data were collected from the Korea National Health Insurance Service between 2006 and 2017. Simple and multiple Cox proportional hazards analyses were performed. The death data of Koreans from 2006 to 2018 were used. Results The mean age of patients with MFS was 27.2± 16.8 years, 26.5± 15.9 years for males and 28.2± 18.1 years for females (P < 0.01), and the proportion of males was 59.5%. The age-standardized incidence and prevalence in 2017 were 0.51 and 5.70 per 100,000 persons, respectively. The 10-year survival rate was 92.7%. Adjusted hazard ratio increased significantly with age, male sex, heart failure, ischemic stroke, hemorrhagic stroke, chronic kidney disease, malignant neoplasm, aortic dissection, and abdominal aortic aneurysm. Conclusion Although the overall 10-year survival rate of MFS was over 90%, the adjusted hazard ratio was significantly higher in the older age group, male sex, and individuals with heart failure, stroke, chronic kidney disease, malignant neoplasm, aortic dissection, and abdominal aortic aneurysm. These results suggest the need for meticulous surveillance of aortopathy in patients with MFS, as it may portend a worse prognosis in aortic dissection and aneurysm, and in older age groups with MFS.